SHAZAM Community
Ask Your Question

Revision history [back]

For a fixed constraint you can substitute the constraint into the equation. e.g.

Y = a + bX + (1-b)Z becomes Y = (a-1) + b(X-Z)

It might be worth trying to contact the authors and see if they will share their SHAZAM code.

For a fixed constraint you can substitute the constraint into the equation. e.g.

Y = a + bX + (1-b)Z
becomes

becomes

Y = (a-1) + b(X-Z)

b(X-Z)

It might be worth trying to contact the authors and see if they will share their SHAZAM code.